ZONING OF CLIMATE-AGRICULTURAL DRYLAND WHEAT USING GIS CASE STUDY: HAMEDAN PROVINCE - mohammad ahmadvand; shahriar khaledi; parviz Kardavani (تحقیقات کاربردی علوم جغرافیایی)
Climate and the required parameters for agricultural products are the important factors of production. We can determine potential facilities in different areas and consider the maximum tapping through agricultural meteorology. Due to drylands potentials in Hamedan province, we conducted a comprehensive survey based on 20 years (1995-1995) climatic elements of 9 main and supplementary synoptic stations. Thus, according to wheat phenological conditions and matching those with climatic conditions requirements in Hamedan province, we surveyed effective indices in grow crops. Finally, using geographic information systems (GIS) we implemented climatic elements zoning and weighting. Then the appropriate and inappropriate areas of the province for dryland wheat were determined. Results indicated among the climatic elements, annual rainfall and its distribution during the growing season, also the grow degree day (GDD) are important factors in process of dryland wheat. Based on maps extracted from the GIS, about 18 percent of the areas of province which are located in west, south west including Nahavand, Tuiserkan and Asadabad cities, enjoy very potentials and 46percent medium, 34percent good and 2 percent of Ghahavand city of Hamedan city functions lacks the necessary talent. with no potentials.